Biblioteka akademicka – płaszczyzny ewolucji - Kazan, Anna; Skubała, Elżbieta (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
„Do libraries more and more lose their tangible form and, through entering the virtual world, lose an established identity…?” For one, the answer to a question given in the conference agenda is obvious and unambiguous, with a hint of nostalgia and pejorative evaluation – yes! For others, the positive answer means progress, up-todateness and service quality of library, which in common perception still remains a symbol of „traditional” institution. The range of changes regarding higher schools libraries, following technical development and users expectations, is huge and concerns not only the merits, but also finances, accounting, inventory of the property or human resources managment. Ultimately the mission of an academic library and its role at the university may change. With some of those changes librarians are already familiar and therefore – ready for the effects. But some of those modifications may still be surprising. In the article we will analyse some of the library activities, which – due to technological evolution – are transfered to virtual world. We will also try to guess a direction in which academic libraries should begin to change.